Autosomal dominant polycystic kidney disease: A case report (Indian Journal of Case Reports, 2021)
Autosomal dominant polycystic kidney disease (ADPKD) is an inherited condition that causes small fluid-filled sacs called cysts to develop in the kidneys. ADPKD affects 1 in 500–1000 people. We report the case of a 70-year-old male patient with complaints of difficulty in passing urine, lower abdominal pain, fever with chills, and hematuria. The ultrasonography report of the abdomen and pelvis showed bilaterally mildly enlarged kidneys with multiple variable simple cysts slightly distorting the normal renal architecture and mildly increased residual visualized cortical echoes concerning adult polycystic kidney changes. The therapeutic regimen was targeted to treat the symptoms of the patient. In India, there is a need for epidemiological studies on ADPKD since insignificant data are present that could rationally reflect its prevalence and incidence, for which this case report could be utilized.